Pengaruh Organizational Learning terhadap Peningkatan Hard Skills, Soft Skills dan Inovasi Guru - Francisca Sestri Goestjahjanti; Agus Purwanto; Masduki Asbari; Laksmi Mayesti Wijayanti; Choi Chi Hyun; Eva Agistiawati; Miyv Fayzhall; Fatrilia Rasyi Radita; Siti Maesaroh; Mustofa Mustofa; Sri Wahyuni Asnaini; Gusli Chidir; Winanti Winanti; Ahmad Yani; Eman Singgih; Rachma Nadhila Sudiyono; Sucipto Basuki; Teguh Yuwono; Dhaniel Hutagalung; Wulan Rahma Dewi (Universitas Muhammadiyah Enrekang, 2020)
This study aims to measure the influence of organizational learning on the improvement of hard skills, soft skills and teacher innovation capability in Indonesia.Hard skills and soft skills as mediated variables. Data collection was carried out by simple random sampling via electronic to a population of teachers in Jawa Barat. The returned and valid questionnaire results were 663 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are organizational learning has a positive and significant effect on teacher innovation capability, both directly and through mediating hard skills and soft skills. This novel research is proposing a model to build teacher innovation capability among teachers through organizational learning with hard skills and soft skills as mediation. This research can open the way to improve teacher readiness in facing the era of education 4.0.